Emergent Developmental Evaluation Developments - Michael Q. Patton (Journal of MultiDisciplinary Evaluation)
Background: Developmental Evaluation (DE) continues to develop. After reviewing the niche and history of DE, this article identifies five new and emergent purposes for DE to add to the original five – and forecasts future developments for diverse, innovative, and adaptive DE applications. An extended example of DE in supporting pivoting in the pandemic illustrates DE as adaptation to crisis as distinct from supporting social innovation.